EFEKTIVITAS PENERIMAAN PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB P2) TERHADAP PENINGKATAN PENERIMAAN PENDAPATAN ASLI DAERAH (PAD) (Studi Pada Dinas Pendapatan Dan Pengelolaan Keuangan Kota Surabaya) - Saputro, Rudi (Jurnal Mahasiswa Perpajakan, 2014)
UU Number 28 year 2009 was born to change the system to collect Land and Building Tax in Village and City urban sector. It has begun as kind of centre tax that run by Directorate General of Taxes, since 2011 it has given to the local region where is the revenue of Land and Building Tax is belong to region totally 100%. Surabaya is one of pilot project where implying the new regulation so that is importantly to know how far the effectiveness of Land and Building Tax revenue in Surabaya. This research used descriptive research. The result of this study showed the average effectiveness of Land and Building Tax revenues which is handled by Directorate General Taxes is upper hand. The average effectiveness of Land and Building Tax revenue is amounted to 86,45% for 2009-2010 with the requirement of interpretation score is effective enough, mean while the average effectiveness of Land and Building Tax revenue in Surabaya is amounted to 76,38% for 2011-2013 with the requirement of interpretation is less effective.Â  The potential of Land and Building Tax in Surabaya is always increase for 2014-2016. Based on that, DPPK Surabaya should work hard to optimize the local revenues come from Land and Building Tax in City sector. Keyword: Land and Building Tax Surabaya, Land and Building Tax in City, Land and Building Tax Decentralised